Breeding for resistance and biocontrol of wilt disease in Curcuma alismatifolia gagnep. by Bacillus spp. - W. Tera-arusiri (2018)
The objectives of this study were to breed for resistance of Curcuma alismatifolia Gagnep. to wilt disease caused by Ralstonia species, by screening and collecting virulent isolates of Ralstonia. Moreover, in order to preserve the value of these ornamental flowers, and to reduce the dependence on toxic chemicals required to combat this disease the biocontrol potential of bacteria antagonistic to Ralstonia, was investigated. Over 500 bacterial strains, isolated from soil, leaf surfaces of C. alismatifolia Gagnep. and hot springs in the Chiang Mai province in Thailand, were screened in vitro for antagonistic activity against R. solanacearum. Three isolates providing growth inhibition in vitro, were identified as Bacillus licheniformis, B. amyloliquefaciens and B. subtilis. Subsequently, these isolates were used for biocontrol in planta. One of the isolates, B. subtilis was shown inhibition greater than 70% when compared with the control and provided a statistically significant growth suppression of the wilt disease on the curcuma. Moreover, all of the antagonistic bacteria isolates were selected to against Anthracnose caused by Colletotrichum sp. in planta. The highest levels of the Anthracnose disease suppression occurred using B. licheniformis and B. subtilis on curcuma flower. The present results indicate that B. licheniformis, B. amyloliquefaciens and B. subtilis could be used to inoculate and reduce the symptoms of disease on Curcuma alismatifolia Gagnep.